An examination of ironic effects in air-pistol shooting under pressure - Gorgulu, R. (Journal of Functional Morphology and Kinesiology, 2019)
This study aimed to test the incidence of ironic performance errors in elite air-pistol shooters. Previous research has revealed that, when shooters are anxious, avoidant instructions can cause ironic performance breakdown, especially in the unintended direction. Fifty-seven experienced air-pistol shooters were given specific instructions not to shoot to a certain part of a target, under low- and high-anxiety conditions, respectively. Results demonstrated that, when instructed not to shoot in a specific direction, anxious shooters did so a significant number of times. Interestingly, there was no difference in non-target non-ironic error, which provides specific support for Wegner`s theory of ironic processes of mental control in air-pistol shooting. Consequently, these findings illustrated that the combination of increased anxiety with avoidant instructions could lead to such unintended performance errors, called ironic error. Thus, understanding the mechanism of the anxiety-performance relationship may be a useful theoretical framework which could provide practical, instruction-based interventions to reduce susceptibility to ironic errors under pressure.